Analisis Prioritas Rehabilitasi Terumbu Karang Berbasis SST dan Coral Bleaching di Pulau Liwungan, Pandeglang, Banten - Muhammad Romdonul Hakim; Muhammad Yusuf; Rizqi Rizaldi Hidayat; Nur Ikhsan (Geosfera: Jurnal Penelitian Geografi, 2026)
Coral reef ecosystems are highly vulnerable to increases in Sea Surface Temperature (SST), which can trigger coral bleaching events. This study aimed to analyze SST dynamics, examine the relationship between SST and coral reef conditions, and identify rehabilitation priorities in Liwungan Island using Landsat 8 and 9 imagery acquired between April 2023 and 2025 and processed through Google Earth Engine (GEE). Rehabilitation priorities were determined using a pixel-based spatial analysis with a cumulative scoring system integrating thermal stress intensity, represented by Degree Heating Weeks (DHW), and changes in healthy coral cover. The results revealed a decreasing SST trend during the observation period, accompanied by a reduction in bleaching risk and an increase in healthy coral cover in 2024–2025. Linear regression analysis demonstrated a strong relationship between SST and healthy coral cover (R² = 0.7847), indicating that SST is a major driver of coral reef condition. The integration of thermal stress and coral cover change successfully identified three rehabilitation priority classes: Urgent (3.97 ha), Alert (167.89 ha), and No Action Required (10.53 ha). This study provides a spatially explicit framework that integrates SST dynamics and bleaching risk to support adaptive coral reef rehabilitation planning. The findings demonstrate the potential of GEE-based remote sensing for evidence-based coastal management, although field validation remains necessary to improve result reliability.